Análisis de los indicadores de acreditación de la carrera de Informática Aplicada a la Educación al año 2015. criterios de estudio: plan curricular y estudiantes - Quisi Aragadobay, Luis Rodrigo (2016)
The Department of Institutional Assessment and Accreditation begins the evaluation process of some programs in the College of Education, so the program called Applied Informatics begin the process of organization and collection of evidence. It was noted that there are redundant processes when collecting information, different departments delay the delivery of information, they sometimes take days, weeks and even months, all these problems are generated because there is no modeling of optimal processes, to ensure the information flow. The aim of the project is to propose a process management model for curriculum and students plan indicators. For this research evidence of the curriculum criteria and students using the assessment model learning environment education careers proposed by the CEAACES was collected, it was also considered the analytical method as it is to analyze the criteria, sub criteria, indicators the research is documentary as indicators of accreditation will be documented for the program called Applied Informatics. Once the evidence was collected, is determined that the level of compliance with the criterion Curriculum is 78.25%, and the criteria students have a 69.99% compliance. Keywords: Accreditation criteria, self-assessment, indicators, CEAACES, higher education, evidence.